The Effect of Disposable Mask Waste on Environmental Pollution in the Pandemic Era in Surakarta City - Hashfi Hawali Abdul Matin; Jilan Ashila; Layyinatussyifa A’yuni Fatikha; Maulyda Shofa Azizia; Muhammad Fadhillah Armando; Muhammad Reynaldi Putrayuda; Nimas Wahyu Silaningtyas (Diponegoro University, 2022)
The Covid-19 virus was recorded to have been found in Indonesia since March 2, 2020. This virus is a virus that is easily contagious, so it is one of the efforts to prevent transmission by using a mask. so that everyone is required to wear a medical or non-medical mask when doing activities outside the home. Of the two types of masks that are more often used, namely the type of medical masks that are used because they are considered safer and more comfortable than non-medical masks. However, after use, the mask turns into the garbage which is classified as B3 waste. Hazardous waste has different characteristics and properties from waste in general because it is unstable, reactive, explosive, flammable, and toxic. In this case, once the mask waste is immediately disposed of without processing, the environment can be explained. Therefore, this study was conducted with the aim of knowing the effect of disposable medical waste on environmental pollution during the pandemic era in Surakarta City. The method used in this study is a questionnaire method which was conducted through online media surveys targeting people aged 17-25 years and supported by data from indexed literature studies. The results of this study indicate that out of a total of 45 respondents, the community is very aware of B3 waste (80%), knows that B3 waste is harmful to health (100%), likes disposable medical masks (58%), understands disposable medical waste including B3 waste. (82%). Meanwhile, for the management of disposable mask waste, it shows that people still store medical mask waste at home (93%), understand the proper disposal of disposable mask waste (78%), have not differentiated it from other waste (60%), have not implemented 3R (76%) ) ), cutting medical waste before disposal (78%), understanding that medical mask waste is harmful to the environment (100%).